PENERAPAN PENDEKATAN PAKEM DENGAN METODE DEMONSTRASI DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS IV SDN KANDRI 2 KOTA SEMARANG (THE IMPLEMENTATION OF PAKEM APPROACH BY USING DEMONSTRATION METHOD IN TEACHING SOCIAL SCIENCE TO - Kurniasari, Ajeng Wahyu (Universitas Negeri Semarang, 2011)
Based on the initial observation held at SDN Kandri 2 Semarang, it was found that there was a problem with the teaching process. The teacher just gave too short explanation about the passage and the students were asked to read the more complete passage in the studentsÃ¢â‚¬â„¢ worksheet by themselves but the teacher didnÃ¢â‚¬â„¢t give them more explanation and intensive guidance. As a consequence, it resulted in the studentsÃ¢â‚¬â„¢ achievement. The students couldnÃ¢â‚¬â„¢t reach minimum completeness grade criteria. All of them got under 60. The implementation of PAKEM approach by using demonstration method is expected to improve the studentsÃ¢â‚¬â„¢ achievement in Social Science class. The class action research is applied in a four step cycle consists of planning, application, observation, and reflection. The PAKEM approach was implemented in those four steps. The subject of the research is the students of fourth grade of SDN Kandri 2 Semarang. There are 13 students. The focuses of the research are teacherÃ¢â‚¬â„¢s skill, studentsÃ¢â‚¬â„¢ activity, and studentsÃ¢â‚¬â„¢ achievement. The tools for gathering data are observation, test, and documentation. The technique of data analysis in this class action research is descriptive analysis. The result of the analysis shows the teacherÃ¢â‚¬â„¢s skill in cycle I is 56,25%, itÃ¢â‚¬â„¢s Ã‚Â enough. The cycle II is 72%, is belongs to good category, and the cycle III is 91% itÃ¢â‚¬â„¢s excellent. The result of the studentsÃ¢â‚¬â„¢ activity in cycle I is 63% ; itÃ¢â‚¬â„¢s enough, cycle II is good with 70%, and 92% for cycle III is excellent. The completeness in initial condition was only 5 of 13 students reached the minimum completeness criteria. The average of studentsÃ¢â‚¬â„¢ learning result in the implementation of PAKEM approach by using demonstration method in Social Science teaching is 69 in cycle I with classical completeness 61,5%, while the cycle II is 74,6% with classical completeness 77% and is cycle III is 86,9 with classical completeness 92,3%. Based on the result above, it is suggested the demonstration method should be implemented to all grades and need to be experimented in other lessons. Keywords: PAKEM approach, demonstration method, Social Science, and studentsÃ¢â‚¬â„¢ achievement.